Ethics of Leadership and Political Crisis in the Caliphate of Ali ibn Abi Thalib: A Socio-Civilizational Perspective - Toedien, Faisal Amir; Syamruddin Nasution (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study examines the ethical dimensions of leadership and the political crises that occurred during the caliphate of Ali ibn Abi Thalib (656–661 CE) within the framework of early Islamic social history and civilization. The governance of Ali unfolded amid a profound crisis of legitimacy and communal disintegration following the assassination of Caliph Utsman bin Affan. This research employs a descriptive qualitative approach, integrating historical and sociological analysis of classical sources alongside contemporary studies, using a library-based research design. The findings indicate that Ali’s leadership was rooted in principles of justice, knowledge, and high moral integrity. However, this political idealism frequently confronted a power landscape shaped by intrigue and competing interests. The Battles of Jamal and Shiffin, as well as the arbitration (taḥkim), illustrate how political conflict transformed into theological and social crises that contributed to the emergence of early Islamic sects such as the Khawarij, the Shi’a, and the Murjiʾah. These findings affirm that the leadership ethics of Ali ibn Abi Thalib represent an Islamic political vision grounded in justice, consultation, and the public welfare, while also offering moral insights for the development of contemporary Islamic leadership.